ANALYSIS OF PARAMETERS FOR THE FORMATION OF TURKEY LIVE WEIGHT IN DIFFERENT GENOTYPES - Катеринич, О. О. (Scientific Progress & Innovations, 2014)
It was done a weekly assessment of young turkey live weight of initial lines and hybrids derived from their use. The parameters of the growth of live weight were determined - the intensity of formation (∆t), uniformity index (Ip) and voltage index (IH). Established sex and genetic differences according to the nature of forming of turkey live weight of paternal lines cross "Kharkiv". Established a significant level of voltage index in predicting growth of turkey live weight in the 16 - weeks of age (r = 0,72; -0,60).